Pneumonia detection in chest X-ray images using convolutional neural networks - Şimşek, Çağdaş; Özkorucuklu, Suat; Işıldak, Bora (The European Research Journal, 2025)
Objectives: Pneumonia ranks among the infections and presents a considerable health threat, especially in certain age groups and developing countries. The accurate diagnosis of the disease and prompt identification are crucial for treatment purposes. This study aimed to develope a convolutional deep neural network model that can detect pneumonia using a sufficient number of chest X-ray images that have been verified with a "definite diagnosis" clinically. Methods: This study uses a dataset that includes 1000 chest X-ray images from a variety of age groups taken as part of patient care at Koç University Faculty of Medicine Hospital Clinics. The dataset sample includes two sets of pictures called normal and pneumonia infected. Various preprocessing techniques were used on the obtained images, thus enabling the training and testing of our developed prediction model. Results: We improved the accuracy of the model’s decisions by applying image processing techniques, successfully achieving high levels of decision accuracy with our model We have elevated the precision of decision-making in our model to outstanding levels and achieved impressive F1 Score and AUC (Area Under the Curve) values (F1 Score: 0.94 and AUC Score: 0.98). Conclusions: Our model was trained using X-ray images produced from the same devices of the same hospital and achieved very high prediction results, but using images produced from different countries, different hospitals and different devices, especially training and testing the model with much larger data sets, is a necessary need for this study and the model we developed to become more universal, and in this sense, there is a need to develop and expand the study.